PENGARUH KETERAMPILAN MENGAJAR GURU DAN DISIPLIN BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA KELAS VIII MATA PELAJARAN IPS DI SMP NEGERI 1 TANAH JAWA - Maya Vita Lina Sihotang; Anton Luvi Siahaan; Paulina Herlina N. Sirait (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The success of learning activities at school can be seen from the achievement of student learning outcomes. Student learning outcomes are influenced by several factors including teacher teaching skills and student learning discipline. This research aims to analyze and describe the influence of teachers' teaching skills and student learning discipline on student learning outcomes at SMP Negeri 1 Tanah Jawa.This research is descriptive quantitative research with research sampling using probability sampling techniques; simple random sampling. Hypothesis testing in this research uses multiple linear regression, partial test (t), simultaneous test (F), and coefficient of determination test (R2).The results of the research show that: (1) There is a negative and significant influence between the teacher teaching skills variable and the learning outcomes of class VIII students in social studies subjects at SMP Negeri 1 Tanah Jawa. This is proven in the results of hypothesis testing for the teacher teaching skills variable (X¬1 ¬) it is known that the tcount value is -3.815 < 1.981. (2) There is a significant influence between student learning discipline variables on the learning outcomes of Class VIII students in social studies at SMP Negeri 1 Tanah Jawa. It can be proven in hypothesis testing for the student learning discipline variable (X2) it is known that tcount is 3.046 > ttable value 1981, so it can be concluded that Ha1 is accepted and H0 is rejected. In particular, it is stated that there is an influence between the student learning discipline variables (X2) on student learning outcomes (Y). (3) There is a significant influence of teacher teaching skills and student learning discipline on the learning outcomes of class VIII students at SMP Negeri 1 Tanah Jawa with the results of hypothesis testing in the f-test obtained Fcount of 11,133 > Ftable of 3.08. So, based on the results of the calculations above, it can be concluded that Ha3 is accepted and H03 is rejected, so that the variables teacher teaching skills and student learning discipline together or simultaneously have a significant influence on student learning outcomes.Based on the research results, it was concluded that the teacher's teaching skills and student learning discipline had a significant effect on the learning outcomes of class VIII students at SMP Negeri 1 Tanah Jawa